CURRENT STATE OF CRYPTOCURRENCIES AND POSSIBILITIES OF THEIR USING IN THE WORLD ECONOMY - Мороз, Владислав; Атаманчук, Зорина (SWorldJournal, 2021)
The place and role of cryptocurrency in the world economy is clarified in the article; the importance of new technologies in the development of economic systems is substantiated. Options for the use of cryptocurrencies as financial instrument and new tech